Control effect of pressure-unloaded speed on gas expansion energy released by tectonic coal during coal and gas outburst - Jingyu JIANG; Xiaoning SHI; Chenghao WANG; Yuanping CHENG; Yiming HUANG (Meitan xuebao)
The majority of coal and gas outbursts (referred to as outbursts for brevity) occurred in tectonic coal seams. Gas expansion energy stands out as a critical factor contributing to these outbursts. The development stages involve the rapid release of confining pressure within the coal. To elucidate the mechanism of how pressure-unloaded speed controls gas expansion energy during the continuous development of outbursts, we conducted triaxial loading tests, sieving experiments, and gas desorption measurements on the outburst coal samples from the No.13 Mine of the Pingdingshan coalfield, a site with complex geological structures and significant challenges in managing outburst hazards, at different pressure-unloaded speed. Based on the experimental results, we revealed the pulverization characteristics and gas desorption behavior of tectonic coal under different pressure-unloaded rates. Gas desorption volume and gas expansion energy of crushed coal at different pressure-unloaded speeds were back-calculated, proposing a positive feedback model for the continuous development of outbursts. The results indicate that unloading confining pressure weakens the strength and deformation resistance of coal, with this effect intensifying as pressure-unloaded speed increases. As pressure-unloaded speed increases, the degree of pulverization and gas desorption volume increase, resulting in a corresponding rise in gas expansion energy. When pressure-unloaded speed increases from 0.01 MPa/s to 0.1 MPa/s, gas expansion energy increases by 21.05% to 40%. As the unloading rate increases, the degree of fragmentation in the tectonic coal samples, the gas flow pathways, and the internal energy of the coal also increase. This leads to a higher initial gas desorption volume, ultimately increasing gas expansion energy. The positive feedback cycle involving pressure-unloaded speed emerges as a crucial factor influencing the continuous development of outbursts. It is shown that the positive feedback cycle process of pressure-unloaded speed controlling gas expansion energy is an important factor influencing the continuous development of tectonic coal seam outbursts.